DEVELOPMENT OF WIRE GASKET ON MODERN ELECTRONICALLY CONTROLLED WEAVING MACHINE - Abduraxmonov A.A; Yusupova N.B; Umarova Sh.R; Siddiqov P.S (Scholar Express Journal, 2023)
In this article, the patterns and peculiarities of Uzbek national fabrics, the essence of the colors in them, and the types and forms of new types of pattern design are considered.
Keywords: pattern; peculiarities; fabrics; colors